Pengaruh Urbanisasi Terhadap Penurunan Kemiskinan di Indonesia - Zara Hadijah; Mohammad Isnaini Sadali (Department of Urban and Regional Planning, Diponegoro University, 2020)
Urbanization and poverty are two important aspects closely linked to sustainable development goals. Urbanization in Indonesia is still far from improving migrant welfare as well as their destination regions. Every 1% growth of urbanization in Indonesia can only increase 4% of GDP per capita. Low economic benefits resulted from urbanization in Indonesia merely shift rural poor to become urban poor. The purpose of this study was to analyze the effect of urbanization on poverty reduction in Indonesia, both in the regional aggregate and at the rural and urban levels as the origin and destination regions of urbanization. This study used secondary data of population and poverty from Population Census (SP), the Inter-Census Population Survey (SUPAS), and the National Socio-Economic Survey (SUSENAS). Data analysis was performed using regionalization techniques, Primacy Index, Lorenz Curve, Geographic Information System (GIS), and simple linear regression. The results showed that the rate of urbanization had a positive relationship with per capita income and the population of urban poor, but had a negative relationship with the population of rural poor. A unit increase in urban population variable percentage would increase the average GDP/capita variable by 0,466. This would be followed by an increase in the average urban poor population variable by 0,447 and a reduction in the average rural poor population variable by 0,705.